The Ars interrogandi in the Judicial Examination (cc. 1534; 1558–1571) - Oetjen, Steven G. (The jurist, 2023)
The instruction phase is a crucial part of the canonical judicial process, as it is particularly aimed at uncovering the truth of the controverted matter by providing the judge(s) the proofs necessary to make a correct judgment. Canon law envisions that most of the proofs in a trial usually come from the judicial examinations of parties and witnesses. The norms governing the judicial examination help to ensure that it is carried out in a way that is just and aimed at uncovering the truth. Beyond these norms—and in accordance with them—there is also the ars interrogandi, the art of questioning in a way that best uncovers the truth. This article seeks to develop the art of questioning in the judicial examination, drawing from both canonical and forensic literature.